DUKUNGAN DAN BEBAN KELUARGA DENGAN KEMAMPUAN KELUARGA MERAWAT PASIEN RESIKO PERILAKU KEKERASAN DI KLINIK JIWA RUMAH SAKIT JIWA PROVINSI JAMBI TAHUN 2017 - Vevi Suryenti (Jurnal Psikologi Jambi, 2018)
INTRODUCTION Estimated around 26 million people in the world will experience schizophrenia. Schizophrenic patients often experience violent behavior. data from Jambi Province Mental Hospital showed that the number of violent behavior risk cases in 2016 was 851 people. The purpose of this study is to determine the relationship of support and family burden with the ability of family caring for the patient risk of violent behavior.METHOD This research is a quantitative research with cross sectional design. The population in this study as many as 222 people with a sample of 67 people. Sample collection using accidental sampling technique, and was done in August 2017. Data were obtained by interview using questioner and univariate and bivariate analyzed by chi-square test.RESULT The results of the study were 67 respondents, most of them had good ability in treating the patient about the risk of violent behavior as many as 39 people (58.2%), most respondents had poor family support as many as 37 respondents (55.2%), most of the respondents had a heavy family burden of 36 respondents (53.7%). The result of statistical test shows that there is a relation of family support (p-value = 0,048) and family burden (p-value = 0,000) with ability of family to care patient risk of violent behavior at Mental Clinic of Mental Hospital of Jambi Province Year 2017. CONCLUSION AND RECOMMENDATION It is hoped that the Mental Hospital of Jambi Province routinely extends to the family about the patient with the risk of violent behavior and provides counseling place for the family of soul patients. Keywords: family support, family burden and risk of violent behavior